The Transformative Power of the Action Research Process: Effects of an Inquiry Approach to Preservice Teacher Education - Clare Kosnik (Networks: An Online Journal for Teacher Research, 1999)
What you see is not always what you get! Having been involved in action research in preservice teacher education for the last four years I continue to be startled by the impact of the process on students and faculty. It is not simply an assignment to be completed; rather, it is a process that leads student teachers to the core of what it means to be a teacher. This experience and the knowledge gained in turn change them as individuals. The action research process requires students to ponder and struggle with many difficult questions: what is the role of the teacher; what does it mean to have a student-centred class; how much can and should I deviate from the formal curriculum; how can I authentically assess student learning; what should be the goals of schooling; and what kind of teacher do I want to be? These deep issues require a lifetime of reflection, analysis and research. Certainly student teachers do not "solve and answer" these questions; however, action research draws them into the intricate process of teaching/learning and helps them realize that teaching is a highly personal process.